RETRACTED: Challenges Faced by Non-major Students in Learning English to Achieve the Outcomes at a Vietnam Public University - Linh, Nguyen Thuy; Hang, Pham Thuy (VNU Journal of Science: Education Research, 2025)
English has been a subject of research for many years, and numerous studies have been conducted on the difficulties faced by students in learning English. This study seeks to pinpoint the challenges that non-English major students encounter when learning English for learning outcomes at Vietnam public university. Additionally, it aims to offer practical solutions to tackle these challenges. The research methodology relies on distributing questionnaires to 300 second-year students. Analysis of the gathered data reveals that mastering listening skills proves to be the most difficult aspect of English language learning for the participants. Following closely behind are difficulties in writing and speaking skills. Moreover, a noteworthy finding is that a majority of respondents lack confidence in their ability to communicate effectively in English. Potential remedies include implementing language workshops, utilizing interactive learning tools, and providing immersive language experiences. It is imperative to cultivate a supportive learning atmosphere where students feel encouraged to engage in English language practice and improve the confidence of non-English major students at Vietnam public university.